Visual search strategies of expert and novice futsal coaches across game situations - Rodrigues, M. E. F. P.; Leite, N. M. C.; Ribeiro, J. N.; Sampaio, A. J. D. E.; De Araújo, D. F. D. R. B. P.; Travassos, B. F. R. (International Sport Coaching Journal, 2026)
Introduction : This study aimed to compare the visual search strategies of expert and novice futsal coaches in different game situations. Data were collected using the Pupil Invisible eye tracker and processed through the Pupil Cloud platform. Methods : Ten expert (ages 48.30 ± 5.85) and 10 novice coaches (ages 40.40 ± 7.92) participated in the experiment, developed in a standardised video analysis task, through the viewing of 71 videos (aerial perspective—third-person view) representative of the various game situations (attack, attack set-pieces, strategic attack, defence, defence set-pieces, and strategic defence). The visual search strategies were compared for the number and duration of fixations per second using Mann-Whitney test and the visual search strategies, taking into account the different moments of the game for each group, were compared using the Kruskal-Wallis test. Results : The results suggested different visual exploration behaviours between the groups, with the experts showing a general lower number of fixations, but of longer duration. Also, distinct visual search strategies were identified according to the game situations. Discussion and Conclusions : In conclusion, expert and novice coaches revealed different strategies of visual exploration of the game. It seems that expert coaches are more efficient in selecting specific information, particularly in attacking moments, while novices revealed higher variability.